The Resilience of Persons with Disabilities during the COVID-19 Pandemic - Hanjarwati, Astri; Hermawati, Istiana; Akil, Husein Avicenna (Masyarakat: Jurnal Sosiologi, 2022)
The resilience of persons with disabilities throughout the COVID-19 pandemic requires special attention due to their precarious nature. This article complements previous studies on the resilience of various social groups in the face of the COVID-19 pandemic by focusing on (1) The level of resilience of people with disabilities, and (2) The factors that determine such resilience. The resilience of persons with disabilities is measured personally using the The Connor-Davidson Resilience Scale (CD-RISC) developed by Kathryn M. Connor, MD and Jonathan R.T. Davidson, MD. Meanwhile, community resilience was measured using a concept developed by Norris F.H and Steven R.P. This study utilizes a survey method with a research sample of 137 disabled individuals of the organization Persatuan Bangkit Bersama(PBB) and the Yogyakarta Paraplegic Association (P3Y) in Yogyakarta. Data was retrieved through questionnaires distributed as a Google Form link via WhatsApp. The results showed that the resilience of persons with disabilities during the COVID-19 pandemic was in the high (52.6%) and moderate (47.4%) categories. The determinants of resilience are (1) external factors in the high category (68.6%) and medium category (31.4%); and (2) internal factors in the high (45.3%) and medium (54.7%). The most significant factors for the resilience of persons with disabilities are external ones, namely the carrying capacity of family, friends in organizations, neighbors, government policies, and NGO assistance.